Avaliação do processo de reparo alveolar em ratos pinealectomizados utilizando fluorocromos - Servato, João Paulo Silva [UNESP] (2009)
Studies show that people who work at night shift lose the ability to circadian release of melatonin (Me) by the pineal gland, because this hormone is only released by this gland under conditions of darkness and during sleep. Beyond the control of the circadian cycle, the melatonin has been linked to several specific functions, acting as an antioxidant, an inflammatory and osteogenesis substance. Melatonin may interfere with alveolar repair in different ways, by the modulation of inflammatory processes, by the formation of collagen fibrils, by the differentiation time of osteoblasts, and by oxidative stress. Due to these actions of Me, may be that the night workers, after a tooth extraction, show a delay in wound healing. However, there are no studies that demonstrate this assumption. Therefore, this study aims to evaluate the process of wound healing in pinealectomized rats. For this, it was used 20 Wistar rats with 1 month of age to be divided into two groups: 1) SHAM group, animals underwent sham surgery for pinealectomy, this animal was carried out all procedures of pinealectomy, except the removal of pineal gland; 2) PNX group, the animals that was subjected to pinealectomy (the removal of the pineal gland). After 30 days of pinealectomy was performed for extraction of upper right incisor. After the tooth extraction was injected (im) the fluorochromes: calcein (in 14 days postoperative -PO) and alizarin (in 28 days PO). In 35 days PO, the maxilar containing the alveoli in repair was removed and carried out the processing laboratory. After all the mechanical procedure, analysis of the slices will be made through the epifluorescence microscope, coupled to an external light source for excitation of fluorochromes by using filters specific for photomultipliers to calcein and alizarin, corresponding to the wavelength of excited for each...